Aspek Hukum Diversi Terhadap Anak Penyalahguna Narkotika dalam Sistem Peradilan Pidana Anak Indonesia - Baskoro, Novi E. (Law Study Program, Faculty of Law, Nusantara Islamic University, 2018)
Narcotics abuse is not only a national problem, but has become a global issue (world). Currently the drug abuse has entered all walks of life to transcend gender, economic class, and even the age of the child. Indonesian Government Policy in the handling of drug abuse as stipulated in Law No. 35 Year 2009 on Narcotics is still positioned abusers of drugs as a criminal act by the threat of criminal sanction without distinguishing age limit offenders. Although the Narcotics Act adopts a two-track (double track system), namely imprisonment accompanied by sanctions, the form of rehabilitation. Especially for the handling of child abusers of narcotics under Law No. 11 of 2012 on the Criminal Justice System Child, sought mandatory diversion. Their diversion based on the fact that the criminal proceedings against children in conflict with the law through the formal criminal justice system have caused more harm than good. Consideration do versioned motivated by the philosophy of juvenile justice system, which is toprotect and rehabilitate (protection and rehabilitation) the child offender. In this dissertation research into the identification of the problem is how the legal position of the diversion of narcotics abusers of children in the perspective of development of criminal law and punishment and how the concept of diversion handling of child abusers of narcotics in the juvenile justice system in Indonesia for the foreseeable future. The research specification is using descriptiveanalysiswhich is describing the problems and later evaluating and analyzing them withprimary, secondary and tertiary legal source. The method applied is juridical-normative which testing and evaluating the secondary data. Concerning on this juridical normative method the research passed two stages, the literature research and field research. The data is analyzed by juridical- qualitative analysis where the obtained data analyzed without statistic formulation.